ANALYSIS OF THE MORAL VALUE IN THE NOVEL "IMPERFECT" WRITTEN BY MEIRA ANASTASIA - Fakhirah Nur Inayyah; Marudut Bernadtua Simanjuntak (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The diversity of genres and novel themes in the world, especially in Indonesia, has grown rapidly. In addition to entertainment, the novel also contains a moral message from the author that she wants to convey to her readers. “Imperfect” is a novel by Meira Anastasia, this novel raises the issue of body shaming and the motivation for self-love. This novel tells about Meira, who is the wife of an actor and also a director to appear perfect. Pressure from family, friends, and the environment finally makes Meira feel insecure and hate herself. In this book, Meira tells her anxiety in a language that is flexible and relaxed, she also adds witty illustrations that make this book interesting. This book turns a negative view of an imperfect body into a positive one. This study aims to analyze the moral message contained in the novel "Imperfect". This study uses a qualitative method and will examine and analyze the moral values contained in the novel that can motivate positive change. The results of the research on the novel "Imperfect" have many moral messages such as resilience in dealing with problems such as body shaming, motivation to love oneself, and turning insecurity into gratitude.